Контроль изоляции сетей низкого напряжения методами двух и трех отсчетов вольтметра - Olszowiec, P. (Електротехніка і електромеханіка, 2016)
Представлено применение методов контроля изоляции сетей низкого напряжения постоянного и двойного рода тока
с помощью вольтметра и резистора. Приведены формулы для вычисления сопротивления изоляции методами двух и
трех отсчетов вольтметра. Предложен новый способ двух отсчетов вольтметра для сетей двойного рода тока.
Представлена модификация рассматриваемых методов, ограничивающая их основной недостаток – длительность
переходного процесса. Представлено застосування методів контролю ізоляції мереж низької напруги постійного і подвійного роду струму за
допомогою вольтметра і резистора. Наведено формули для обчислення опору ізоляції методами двох і трьох відліків
вольтметра. Запропоновано новий спосіб двох відліків вольтметра для мереж подвійного роду струму. Представлена
модифікація розглянутих методів, що обмежує їх основний недолік – тривалість перехідного процесу Purpose. In the paper there are described methods of two and three
voltmeter readouts for insulation resistance periodic measurement
in live DC and AC/DC IT networks. A new measuring method for
AC/DC networks is proposed. Application of a novel algorithm for
shortening of measurement cycle is explained. Methodology. All
methods of two and three voltmeter readouts consist in connection
of a resistor and measurement of mean value of network’s fixed
point-to-ground voltages. Results. A new algorithm implemented in
KDZ-3 device enables determination of steady-state voltage of a DC
network’s pole much faster than in other exploited systems. Originality. In author’s modification of two voltmeter readouts method,
line-to-ground voltage mean value is measured at AC side of
AC/DC network. This innovation has not been applied for implementation of periodic insulation monitoring in AC/DC IT networks
yet. Practical value. The use of author’s innovation will allow to
execute measurements at AC side of AC/DC IT networks which
might be necessary if rectifier’s output circuits are unavailable.
Shortening of measurement cycle duration of two or three voltmeter
readouts method’s is of great importance in networks with high
capacitance.